Magnesio-arfvedsonite from Jade Mine Tract, Myanmar: mineral description and crystal chemistry. (2nd January 2018) - Oberti, Roberta; Boiocchi, Massimo; Hawthorne, Frank C.; Ball, Neil A.; Harlow, George E.
Abstract: Magnesio-arfvedsonite, the C Fe 3+ -dominant analogue of eckermannite, has been found in a sample of "szechenyite" in the mineral collection of the American Museum of Natural History (AMNH H35024). It comes from the northern part of the Jade Mine Tract near Hpakan, Kachin State, Myanmar. Associated minerals are kosmochlor–jadeite solid-solution pyroxene and clinochlore. The ideal formula of magnesio-arfvedsonite is A Na B Na2 C (Mg4 Fe 3+ ) T Si8 O22 W (OH)2, and the empirical formula derived from electron microprobe analysis and single-crystal structure refinement for the sample of this work is A (Na0.96 K0.04 )Σ=1.00 B (Na1.57 Ca0.40 Fe0.02 2+ Mn0.01 )Σ=2.00 C (Mg4.26 Fe0.19 2+ Fe0.41 3+ Al0.11 Ti0.03 4+ )Σ=5.00 T (Si7.99 Al0.01 )Σ=8.00 O22 W [F0.02 (OH)1.98 ]Σ=2.00 . The unit-cell dimensions are a = 9.867(1), b = 17.928(2), c = 5.284(1) Å, β = 103.80(2)°, V = 907.7 (2) Å 3, Z = 2. Magnesio-arfvedsonite is biaxial (–), with α = 1.624, β = 1.636, γ = 1.637, all ± 0.002 and 2Vobs = 36(1)°, 2Vcalc = 32°. The ten strongest reflections in the X-ray powder pattern [ d values (in Å), I, ( hkl )] are: 2.708, 100, (151); 3.399, 68, (131); 3.144, 63, (310); 2.526, 60, (202); 8.451, 46, (110); 3.273, 39, (240); 2.167, 37, (261); 2.582, 34, (061); 2.970, 34, (221); 2.326, 33, [(251) (421)].